2007
DOI: 10.1002/mawe.200700239
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of porous calcium phosphate with expanded bone marrow cells using an autologous plasma clot

Abstract: Multipotent human mesenchymal stromal cells (hMSCs) are currently the most promising cell type for regenerative medicine and tissue engineering. For clinical applications with special focus on fracture repair a method to deliver in vitro-expanded bone marrow cells to the fracture site is presented. Autologous blood plasma clotting was used to fix expanded cells and synthetic tricalcium phosphate particles. A jelly-like but solid composite matrix was obtained which could easily be handled by the surgeon. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…It is likely that the presence of different platelet/leukocyte number at the time of gelation profoundly influences the plasma clot structure. We have shown that also nonviable cells are detectable at distinct and localized areas after the clotting process within a plasma matrix which obviously resulted from cell squeezing due to the formation of fibrin fiber bundles [3]. Clots formed in the presence of low thrombin concentrations are composed of thick fibrin fibers, while clots formed in the presence of high thrombin concentrations are composed of thin fibers [25].…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…It is likely that the presence of different platelet/leukocyte number at the time of gelation profoundly influences the plasma clot structure. We have shown that also nonviable cells are detectable at distinct and localized areas after the clotting process within a plasma matrix which obviously resulted from cell squeezing due to the formation of fibrin fiber bundles [3]. Clots formed in the presence of low thrombin concentrations are composed of thick fibrin fibers, while clots formed in the presence of high thrombin concentrations are composed of thin fibers [25].…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, there are few drawbacks with the use of plasma clots which consist of completely autologous material. In contrast to commercially available fibrin matrices or sealants which are adjustable in matrix strength by using different concentrations of fibrinogen and thrombin [24], an autologous plasma clot is more heterogeneous in its microstructure [3]. Here, varying factors will influence the dynamic process of the clot formation which includes the content of platelets and/or leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations